Sociocultural adaptation process of international graduate students at a university in southern Chile. - Sarmiento Quiñones, Astrid Vanessa; Bustos Navarrete, Claudio; Vergara Del Solar, Jorge Iván; Salazar Alvarado, María Amalia; Bravo, Cecilia (Journal of Human Behavior in the Social Environment, 2025)
Chile has a growing migrant presence, including at universities. As migration involves adjusting to new demands, this study aims to understand international graduate students' sociocultural adaptation in a southern Chilean city using qualitative phenomenological research. Thirteen semi-structured interviews were analyzed via interpretative phenomenological analysis (IPA). Findings show migration decisions are influenced by home country social factors and academic/cultural growth objectives in Chile, impacted by contextual, cultural, social, and intrapersonal elements. Students manage threats using emotional regulation, acculturation strategies, and sense-making coping. Supportive social environments also protect, offering valued conditions. In conclusion, adaptation involves individual coping strategies and host society social factors. The paper discusses recommendations for future research.